2018
DOI: 10.1177/1748006x18799907
|View full text |Cite
|
Sign up to set email alerts
|

Selective maintenance optimisation considering random common cause failures and imperfect maintenance

Abstract: This article addresses a selective maintenance optimisation problem for systems subject to random common cause failures. A system is likely to suffer from several random common cause failures during a given mission. Random common cause events, which occur with a specific probability distribution, may result in the simultaneous failures of multiple elements. Because time is one of the most crucial maintenance resources, a time-based imperfect maintenance model is proposed to quantify the maintenance efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Up to now, two types of imperfect maintenance models are popularly adopted, that is, effective age and failure rate function respectively. 36 Kijima et al 37 first proposed the concept of virtual age in quantifying the impact of maintenance on repairable systems, and in the literature the concept of effective age has been more widely used than the virtual age. It is worth pointing out that the effective age and the virtual age are essentially the same in the maintenance field.…”
Section: Probabilistic Updating Under Imperfect Maintenancementioning
confidence: 99%
“…Up to now, two types of imperfect maintenance models are popularly adopted, that is, effective age and failure rate function respectively. 36 Kijima et al 37 first proposed the concept of virtual age in quantifying the impact of maintenance on repairable systems, and in the literature the concept of effective age has been more widely used than the virtual age. It is worth pointing out that the effective age and the virtual age are essentially the same in the maintenance field.…”
Section: Probabilistic Updating Under Imperfect Maintenancementioning
confidence: 99%
“…By considering the uncertainty of maintenance quality in multi-state manufacturing systems, Chen et al 27 presented a type of novel optimization model for selective maintenance. Cao et al 28 studied selective maintenance optimization problem for the systems subject to random common cause failures, a genetic algorithm and Monte Carlo simulation approach were proposed to solve the optimization model. It indicated that the proposal of time-based imperfect maintenance model can yield better maintenance results.…”
Section: Introductionmentioning
confidence: 99%
“…Coolen and Coolen-Maturi 22 study the system reliability following CCF of components by non-parametric predictive inference. Cao et al 23 consider a selective maintenance optimization problem for systems subject to random CCF. For the Bayesian-based methods, Qiu and Ming 24 study the system affected by the probabilistic common cause failure under different relationships.…”
Section: Introductionmentioning
confidence: 99%